2015
DOI: 10.2174/1874312901509010008
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Five Year Out-Come in Two Cohorts of Patients with Early Rheumatoid Arthritis – A BARFOT Study

Abstract: Abstract:The objective of the study was to compare disease characteristics over the first 5 years of disease in patients with RA, with disease onset in 1990s and 2000s, respectively.Methods: All 2235 patients with early RA (disease duration ≤12 months) were recruited from the BARFOT prospective observational study. These patients were divided into group 1 included 1992 to 1999 (N=1084, 66% women) and group 2 included 2000 to 2006 (N=1151, 69% women). Disease Activity Score (DAS28), VAS pain and Health Assessme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
(32 reference statements)
0
2
0
Order By: Relevance
“…Especially, the HAQ-scores were notably worse in women >70 years (0.9 for PsA and 0.9 for RA) than in women <50 years (0.38 and 0.13) and worse also in men >70 years (0.6 and 0.4) compared to younger male patients (0.1 and 0 in males <50 years old). Our observations are in line with previous research for both PsA and RA and for the general population (11,12). The age-specific HAQ was similar in women with RA, compared to a Swedish study from 2021, as it showed a median HAQ of 0.4-0.6 for women younger than 70 and 0.9 for women over 70, whereas the scores were 0.4-0.6 and 0.9 for women in the same age groups in our study.…”
Section: Haqsupporting
confidence: 94%
“…Especially, the HAQ-scores were notably worse in women >70 years (0.9 for PsA and 0.9 for RA) than in women <50 years (0.38 and 0.13) and worse also in men >70 years (0.6 and 0.4) compared to younger male patients (0.1 and 0 in males <50 years old). Our observations are in line with previous research for both PsA and RA and for the general population (11,12). The age-specific HAQ was similar in women with RA, compared to a Swedish study from 2021, as it showed a median HAQ of 0.4-0.6 for women younger than 70 and 0.9 for women over 70, whereas the scores were 0.4-0.6 and 0.9 for women in the same age groups in our study.…”
Section: Haqsupporting
confidence: 94%
“…All patients fulfilled the American College of Rheumatology (ACR) criteria for classification of RA [19] and had a disease duration of ≤12 months. The patients were treated with DMARDs in accordance with the recommended treatment strategy in Sweden, as described in earlier studies [20]. The patients were assessed according to a structured protocol at inclusion and after 3, 6, 12, 24, 60, 96, and 180 months.…”
Section: Patientsmentioning
confidence: 99%
“…For the BARFOT patients, anti-CCP antibodies were analysed in stored serum from inclusion. Additional details are given elsewhere (23,24). Patient characteristics are shown in Table 1.…”
Section: Clinical Disease Assessmentsmentioning
confidence: 99%